Smartphone-based diagnosis of crop diseases. Project profile. - International Potato Center (International Potato Center, 2019)
A crop disease outbreak requires rapid and specific intervention measures, if large yield losses are to be avoided, but farmers often struggle to identify what is causing the problem. A novel artificial intelligence (AI)-based mobile phone app could provide an effective, low-cost and easy-to-use diagnostic solution.